Politeness Strategies in Political Language - Muhamad Isnaini; Busmin Gurning; Edy Setia (LINGUISTIK TERAPAN, 2015)
This study deals with politeness strategies in political language. The aim of the study is to describe how Indonesian politicians realize politeness in their language. The subject was taken nine parties who have representatives. They come from different parties: Democrat, Golkar, PDIP, PKS, PPP, PKB, PAN, Gerindra and Hanura. Data were classified and verified with reference to the criteria of politeness strategies as determined by Brown & Levinson (1987); cover the bald on record strategy, positive strategy, negative strategy and off-record strategy. The finding show that there were four types of politeness strategies used by Politicians in different of types of illocutionary acts; positive strategy, bald on record strategy, negative strategy, and off-record strategy. The most dominant type of politeness strategies used was positive strategy. The most dominant type was due to fact that speakers in interaction try to get closer the hearers. They use the group identity marker in addressing someone so there is no distance relationship between the speaker and hearer. They also gave the reasons when they speak in order to satisfy the hearer. Key words: politician; political language; politeness strategy